Effectiveness of Science Process Skills in Enhancing Physics Concept Understanding and Student Motivation - Kartika, Ika; Djufri, Elyas; Yulianingsih, Elsa; Widyawati, Ani (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
This study aims to: (1) Determine the effectiveness of the science process skills approach in achieving 75% of students passing the Minimum Competency Criteria (KKM), (2) Assess the effectiveness of the science process skills approach in improving conceptual understanding of static fluids, and (3) Evaluate the effectiveness of the science process skills approach in enhancing student motivation. This research is a quasi-experimental study using a pretest-posttest control group design. The independent variable is the science process skills approach, and the dependent variables are conceptual understanding and physics learning motivation. Sampling was conducted using simple random sampling. Data analysis techniques included t-tests, normalized gain, and effect size. The results show: (1) The science process skills approach was not effective in achieving 75% of students passing the KKM, as only 62.5% of students met the standard, (2) The science process skills approach was effective in improving conceptual understanding of static fluids (sig 2-tailed = 0.000 < α = 0.05, thus Ha is accepted and Ho is rejected), with an N-gain of 0.68 (medium) and an effect size of 1.46, (3) The science process skills approach was effective in enhancing motivation in physics learning, with an N-gain of 0.39 (medium).